Advanced bioactive nanomaterials for diagnosis and treatment of major chronic diseases - Liu, Yongfei; Yi, Yi; Zhong, Chengqian; Ma, Zecong; Wang, Haifeng; Dong, Xingmo; Yu, Feng; Li, Jing; Chen, Qinqi; Lin, Chaolu; Li, Xiaohong (Frontiers in Molecular Biosciences, 2023)
With the rapid innovation of nanoscience and technology, nanomaterials have also been deeply applied in the medical and health industry and become one of the innovative methods to treat many diseases. In recent years, bioactive nanomaterials have attracted extensive attention and have made some progress in the treatment of some major chronic diseases, such as nervous system diseases and various malignant tumors. Bioactive nanomaterials depend on their physical and chemical properties (crystal structure, surface charge, surface functional groups, morphology, and size, etc.) and direct produce biological activity and play to the role of the treatment of diseases, compared with the traditional nanometer pharmaceutical preparations, biological active nano materials don't exert effects through drug release, way more directly, also is expected to be more effective for the treatment of diseases. However, further studies are needed in the evaluation of biological effects, fate in vivo, structure-activity relationship and clinical transformation of bionanomaterials. Based on the latest research reports, this paper reviews the application of bioactive nanomaterials in the diagnosis and treatment of major chronic diseases and analyzes the technical challenges and key scientific issues faced by bioactive nanomaterials in the diagnosis and treatment of diseases, to provide suggestions for the future development of this field.